Plant‐parasitic nematodes as invasive species: characteristics, uncertainty and biosecurity implications. (14th September 2013) - Singh, S. K.; Hodda, M.; Ash, G. J.; Banks, N. C.
Abstract Few species of plant‐parasitic nematodes (PPN) are currently recognised as invasive but this is largely because of insufficient investigation and recognition. We compared the characteristics of PPN with those of invasive species generally, using the propagule pressure, abiotic and biotic factors (PAB) framework. Most PPN had many of the characteristics of invasive species and hence have the potential to become invasive. The most common characteristics included: adaptations for human mediated dispersal; multiple entry pathways; microscopic size; large number of propagules; high fecundity; many or cosmopolitan hosts; short lifecycle; ability to survive harsh or unfavourable conditions; ability to vary sex ratios; and ability to overcome host plant resistance. Information is lacking for many characteristics of many species and their impacts remain unquantified, which leaves some important unanswered questions and challenges for assessing PPN as invasive species. However many economically important PPN species have not been recognised as invasive, even when most of the known characteristics and data suggests they should be.